2017
DOI: 10.15171/jcvtr.2017.28
|View full text |Cite
|
Sign up to set email alerts
|

Quality of surgical scrub in a heart hospital: Do not take it for granted

Abstract: Introduction: The role of scrub in the prevention of post-surgery infections is well-known. This study aimed to investigate the inputs and process of surgical scrub in operating rooms of the largest heart hospital of northwest Iran. Methods: This study took place with a before-after design as a clinical audit in 2014. A check list developed based on national and international standards of surgical hand scrub was used as the study instrument. Checklists were completed by observation of surgical team scrubbing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Several studies of similar type have shown that significance dissimilarities of level of surgical hand scrub compliance. 4,6,10,[12][13][14] This study found that only 13% of respondents had compliance the surgical hand scrub according to the standard checklist criteria of (more than 90% score without missing critical steps).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of similar type have shown that significance dissimilarities of level of surgical hand scrub compliance. 4,6,10,[12][13][14] This study found that only 13% of respondents had compliance the surgical hand scrub according to the standard checklist criteria of (more than 90% score without missing critical steps).…”
Section: Resultsmentioning
confidence: 99%
“…minimum 3 minutes. 9 The most commonly use products for surgical hand antisepsis is chlorhexidine or povidine-iodine containing soaps.1 Abdollahi et al 10 found that compliance with scrub prerequisites 58%, scrub process 68%, 2 minutes scrub time 22% and scrub equipments 55% in pre-test. Dhakal, Angadi & Lopchan 11 claimed that nurses (4.29%) on operation theatre did not scrub hands well to two inch above the elbow and completed the procedure less than 3 to 5 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Checklists and posters appear to be a sustainable and a low-resource intervention; these were very commonly used and appeared to generate some very positive results. 13,18,19,28 However, the low variation and low use of technology in interventions leaves significant room for improvement. We are moving into an era in which “big data” has the ability to drive improvement and technological intervention and, with nearly every patient in Organisation for Economic Co-operation and Development countries owning a smartphone, this appears to be an underutilized way to collect data, perform interventions, and quickly validate them.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the causes of mortality in patients after surgery. The most common cause is the hands of the surgical team (Abdollahi, Tabrizi, Jodati, Safaie, & Moradi-joo, 2017). Perioperative hand hygiene is one of the most critical factors affecting the risk of surgical site infection (SSI) as well as the safety of the medical staff (Tsai, Lin, Huang, Loh, & Wen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical hand wash preparation is recommended by both the Center for Disease Control and Prevention (CDC) and the WHO for preventing SSI in all kinds of surgical procedures. According to the CDC, proper hand washing can reduce the occurrence of nosocomial infections (HCAI) to 30% (Abdollahi et al, 2017). The application of surgical hand washing is recommended by the CDC and WHO to prevent SSI in all types of surgical procedure (Gaspar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%